Harry Potter and the prisoner of Azkaban - Rowling, J. K. (New York Arthur A. Levine Books, 1999)
During his third year at Hogwarts School for Witchcraft and Wizardry, Harry Potter must confront the devious and dangerous wizard responsible for his parents' deaths.
"Year 3"--Spine.
Sequel to: Harry Potter and the Chamber of Secrets.
Keywords: Wizards -- Juvenile fiction; Magic -- Juvenile fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary place) -- Juvenile fiction; Schools -- Juvenile fiction; Wizards -- Fiction; Magic -- Fiction; Schools -- Fiction; England -- Juvenile fiction; England -- Fiction; Fantasy fiction -- Juvenile